Effects of altitude/hypoxia on single- and multiple-sprint performance: A comprehensive review - Girard, O.; Brocherie, F.; Millet, G. P. (Sports Medicine, 2017)
Many sport competitions, typically involving the completion of single- (e.g. track-and-field or track cycling events) and multiple-sprint exercises (e.g. team and racquet sports, cycling races), are staged at terrestrial altitudes ranging from 1000 to 2500 m. Our aim was to comprehensively review the current knowledge on the responses to either acute or chronic altitude exposure relevant to single and multiple sprints. Performance of a single sprint is generally not negatively affected by acute exposure to simulated altitude (i.e. normobaric hypoxia) because an enhanced anaerobic energy release compensates for the reduced aerobic adenosine triphosphate production. Conversely, the reduction in air density in terrestrial altitude (i.e. hypobaric hypoxia) leads to an improved sprinting performance when aerodynamic drag is a limiting factor. With the repetition of maximal efforts, however, repeated-sprint ability is more altered (i.e. with earlier and larger performance decrements) at high altitudes (>3000-3600 m or inspired fraction of oxygen <14.4-13.3%) compared with either normoxia or low-to-moderate altitudes (<3000 m or inspired fraction of oxygen >14.4%). Traditionally, altitude training camps involve chronic exposure to low-to-moderate terrestrial altitudes (<3000 m or inspired fraction of oxygen >14.4%) for inducing haematological adaptations. However, beneficial effects on sprint performance after such altitude interventions are still debated. Recently, innovative `live low-train high` methods, in isolation or in combination with hypoxic residence, have emerged with the belief that up-regulated non-haematological peripheral adaptations may further improve performance of multiple sprints compared with similar normoxic interventions.